Assessment of the "recebo with postre" system - Hernández-Matamoros A.; Pimienta Ingelmo J.; Tejeda Sereno J.F.; González Sánchez E. (7th International Symposium on the Mediterranean Pig, 2012)
The aim of this work is to assess the quality of carcass and meat of pigs fed in free range with feed supplemented (system called "recebo" with "postre"). 205 pure Iberian pigs (18 months old with and an average weight of 111.6 kg at the beginning of the experiment) were used. A group of 102 pigs remained in free range for 85 days on a farm of 126.8 ha (Montanera: MN). Another group of 103 pigs were fed in other farm of 122.5 ha in free range and supplemented with concentrates (with 6.44% of crude fat and 59.3% of oleic acid) at a rate of 983 g per animal/day, for 69 days (Recebo: RC). Once slaughtered, measures were taken in the carcass and composition studies were performed on subcutaneous and intramuscular tissue (20 pigs per group). RC animals have better yields of primal cuts (32.2% for total of hams, shoulders and loins) than MN (28.9%). The longissimus dorsi intramuscular fat is the same statistically in RC (8.41%) than in MN (8.55%). The meat tocopherol composition reflects the diet: α-tocopherol: 4.78 and 2.02 mg/kg and γ-tocopherol: 0.47 and 1.07 mg/kg for RC and MN, respectively. The subcutaneous fatty acids are similar except oleic acid (54.07% in RC and 56.16% in MN).
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)